Review of Reinventing martial arts in the 21st Century, by George Jennings - Sánchez García, Raúl (Revista de Artes Marciales Asiáticas, 2023)
In Reinventing martial arts in the 21st Century (published by Peter Lang, 2023), George Jennings proposes a hybrid online/offline multi-situated ethnography to account for the circumstances of traditional martial arts nowadays. The book is divided in three parts, preceded by an extended an unusual preface about an ethnographic account of the practice of martial arts before, during, and after the COVID lockdown. Parts one and two present different lines of the recent development of traditional martial arts. Part three is clearly different from the other two, offering a well based ethnographic text on the life courses of some martial artists taken as case studies. Along the text, the author poses a well- balanced set of research techniques and sources to ground his analysis. Jennings affords innovative angles to see the current transformation of these cultural practices. Besides, the book points to a myriad of possible directions that the author will surely explore and further develop in future volumes.